Effects of foliar boron application on seed composition, cell wall boron, and seed δ15N and δ13C isotopes in water-stressed soybean plants - Bellaloui, Nacer; Hu, Yanbo; Mengistu, Alemu; Kassem, My A.; Abel, Craig A. (Frontiers in Plant Science, 2013)
Limited information is available on the effects of foliar boron (B) application on soybean seed composition. The objective of this research was to investigate the effects of foliar B on seed composition (protein, oil, fatty acids, and sugars). Our hypothesis was that since B is involved in nitrogen and carbon metabolism, it may impact seed composition. A repeated greenhouse experiment was conducted where half of the soybean plants was exposed to water stress (WS) and the other half was well watered. Foliar boron (FB) in the form of boric acid was applied twice at a rate of 1.1 kg ha-1. The first application was during flowering stage, and the second application was during seed-fill stage. Treatments were water stressed plants with no FB (WS-B); water stressed plants with FB (WS+B); watered plants without FB (W-B), and watered plants with FB (W+B). The treatment W-B was used as a control. Comparing with WS-B plants, B concentration was the highest in leaves and seed of W+B plants (84% increase in leaves and 73% in seed). Seeds of W+B plants had higher protein (11 % increase), oleic acid (27% increase), sucrose (up to 40 % increase), glucose, and fructose comparing with W-B. However, seed stachyose concentrations increased by 43% in WS-B plants seed compared with W-B plants. Cell wall (structural) B concentration in leaves was higher in all plants under water stress, especially in WS-B plants where the percentage of cell wall B reached up to 90 %. Water stress changed seed δ15N and δ 13C values in both B applied and non-B applied plants, indicating possible effects on nitrogen and carbon metabolism. This research demonstrated that FB increased B accumulation in leaves and seed, and altered seed composition of well watered and water stressed plants, indicating a possible involvement of B in seed protein, and oleic and linolenic fatty acids. Further research is needed to explain mechanisms of B involvement in seed protein and fatty acids.